Acetate wheat starch improving blood glucose response and bilan lipid on obesity dyslipidemia mice - Chu Thi Thu Hien; Phu Thi Hoa; Nguyen Hai Thuy; Tran Huu Dung (Universidade de São Paulo, 2023)
Abstract Resistant starch is particularly concerned with beneficial effects in regulating blood glucose concentration and lipid metabolism, reducing the risk of diabetes and cardiovascular diseases. This study aimed to validate the effects of wheat starch acetate containing 32.1% resistant starch on postprandial blood glucose response and lipid profile on obesity, dyslipidemia Swiss mice induced by a high-fat diet. The result showed that there was a restriction on postprandial hyperglycemia and remained stable for 2 hours after meal efficiently comparing with the control group fed natural wheat starch. Simultaneously, when maintaining the dose of 5g/kg once or twice a day for 8 weeks, wheat starch acetate to be able to reduce body weight and blood glucose, triglyceride, cholesterol levels compared to the control group (p<0.05).